High Solar Flux Concentration Water Splitting with Hematite (α‐Fe2O3) Photoanodes. Issue 1 (9th November 2015) - Segev, Gideon; Dotan, Hen; Malviya, Kirtiman Deo; Kay, Asaf; Mayer, Matthew T.; Grätzel, Michael; Rothschild, Avner
Abstract : The water splitting performance of hematite photoanodes is explored under a wide range of light intensities. The photocurrent scales linearly and the photovoltage scales logarithmically with the intensity, showing steeper rate than in photovoltaics, probably due to the enhanced ratio between charge transfer and recombination at high intensities. Hence, light concentration serves as another handle to enhance the efficiency of hematite photoanodes.